Metode Pengembangan Soft Skills Mahasiswa Universitas Darussalam (Unida) Pondok Modern Gontor Di Mantingan Ngawi Jawa Timur Indonesia Angkatan 2015/2016 - , Damanhuri; , Dr. Badarudin, M.Ag (2017)
The purpose of this research is for knowing: (1) How soft skills development method Darussalam University students (Unida) Gontor Mantingan? (2) What are the factors that support and hinder the development of soft skills of students methods Unida Gontor Mantingan? This research included in the qualitative study with extending the data collected as scope for this study and field for this research (field research).The characteristic from the study more closer toward on study cases, because the object of its research, unida students in the business management faculty on management study program period 2015/2016 M, which in mantingan campus. The data that was already collected was then analyzed which been done by organizes data methode. Data collected by using a documentation technique, observation and interview. All the data that has been collected by regulated techniques, we try to sorted, grouped and categorized so that it can be found the theme in accordance with the development soft skills methode for UNIDA students. Based on the results of the researchers analyses concluded that methode which are applied in soft skills development on unida students is with briefing, the assignment, training, habituation, exemplary, escort and humanity. with the humanity approach, program and idialisme. So the students ready to face life in communities. While the supporting factors, is independence, a strong leadership, environmentalists who support advisory, and infrastructure and their partnership with various institutions. Resistor factors is inhibiting factor is the lack of awareness of some students of the importance of the activities held by UNIDA well in the classroom, dormitory and society. Keywords: method; development; soft skills.